Reproductive tract infections among women attending gynaecology outpatient department - Bohara, MS; Joshi, AB; Lekhak, B; Gurung, G (International Journal of Infection and Microbiology, 2012)
BACKGROUND: Women often suffer silently with reproductive tract infections (RTIs) and sexually active young women are particularly susceptible to sexually transmitted Infections (STIs). The study aimed to know the prevalence of reproductive tract infections among married women attending Gynecological Outpatients Department of Tribhuvan University Teaching Hospital (TUTH), Kathmandu, Nepal. MATERIALS AND METHODS: A hospital based crosssectional design was used to investigate RTIs among women attending outpatients department of Gynae and Obstetrics, TUTH from July to November, 2006. A total of 208 samples from 104 women were examined microscopically and culture using standard microbial technique to investigate etiological agents of RTIs. Study samples were selected and examined on the basis of either having discharge or complaints of lower abdominal pain. RESULTS: A total of 208 samples collected from 104 patients were examined and 26% samples were positive for different causative agents of RTIs. Thirty percent of women reported having symptoms related to RTIs and was common in young married women. Nineteen percent had STIs. Thirteen percent had trichomonasis and 7% had gonorrhoea identified in Gram stained smears and cultures. Many women had endogenous RTIs. Bacterial vaginosis was diagnosed in 15% and vaginal candidiasis in 25% of women. CONCLUSIONS: Young married women have a high prevalence of RTIs. Education and outreach programs are needed to reduce embarrassment and lack of knowledge related to RTIs. The low socio?economic status of women appears to have influence on high rate of infections. DOI: http://dx.doi.org/10.3126/ijim.v1i1.6940 Int J Infect Microbiol 2012;1(1):29-33